Mitophagy enhancers against phosphorylated Tau-induced mitochondrial and synaptic toxicities in Alzheimer disease. (December 2021) - Kshirsagar, Sudhir; Sawant, Neha; Morton, Hallie; Reddy, Arubala P.; Reddy, P. Hemachandra
Abstract: The purpose of our study is to determine the protective effects of mitophagy enhancers against phosphorylated tau (P-tau)-induced mitochondrial and synaptic toxicities in Alzheimer's disease (AD). Mitochondrial abnormalities, including defective mitochondrial dynamics, biogenesis, axonal transport and impaired clearance of dead mitochondria are linked to P-tau in AD. Mitophagy enhancers are potential therapeutic candidates to clear dead mitochondria and improve synaptic and cognitive functions in AD. We recently optimized the doses of mitophagy enhancers urolithin A, actinonin, tomatidine, nicotinamide riboside in immortalized mouse primary hippocampal (HT22) neurons. In the current study, we treated mutant Tau expressed in HT22 (mTau-HT22) cells with mitophagy enhancers and assessed mRNA and protein levels of mitochondrial/synaptic genes, cell survival and mitochondrial respiration. We also assessed mitochondrial morphology in mTau-HT22 cells treated and untreated with mitophagy enhancers. Mutant Tau-HT22 cells showed increased fission, decreased fusion, synaptic & mitophagy genes, reduced cell survival and defective mitochondrial respiration. However, these events were reversed in mitophagy enhancers treated mTau-HT22 cells. Cell survival was increased, mRNA and protein levels of mitochondrial fusion, synaptic and mitophagy genes were increased, and mitochondrial fragmentation is reduced in mitophagy enhancers treated mTau-HT22 cells. Further, urolithin A showed strongest protective effects among all enhancers tested in AD. Our combination treatments of urolithin A + EGCG, addition to urolithin A and EGCG individual treatment revealed that combination treatments approach is even stronger than urolithin A treatment. Based on these findings, we cautiously propose that mitophagy enhancers are promising therapeutic drugs to treat mitophagy in patients with AD. Graphical abstract: ga1